Etiology in patients with incidental findings of elevated alanine transminase avtivities - Ali MERT,; Mahmut İLHAN,; Hakan ŞENTÜRK,; Gürkan BAŞARAN,; İbrahim BAHÇECİOĞLU, (Turkish Journal of Gastroenterology, 2019)
-